Characterizing Brand Knowledge and Identification as Predictors of Consumer-Based Brand Equity: Mediating Role of Employee-Based Brand Equity - He, Zijing (Frontiers in Psychology, 2022)
Branding has been a key factor for the software houses, mainly customer expectations for a predicted product and real-time experience. The identity and knowledge of brands set a certain set of expectations in the mind of the consumers and the organization's employees. This study mainly investigates the effects of brand identity and brand knowledge on the EBBE and CBBE. Further, it examined the mediating role of EBBE among these variables. To complete this empirical study, a quantitative survey was conducted using a 30-item survey method to collect data from 243 respondents from China's software houses. The participants were selected based on purposive sampling. Results show that brand identity and brand knowledge are the main constitutes of EBBE, which significantly predicts the CBBE. Findings of the study indicate a significant mediation of EBBE among brand identity and knowledge and CBBE, the dependent variable. The study highlights the importance of employees in building overall brand equity. Training and brand promotion activities would help the organizations build a brand identity that positively contributes to the EBBE. Furthermore, brand identity and brand knowledge are needed to improve the human capital, engagement of employees, and their emotional affiliations with the organizations, ultimately making the brand equity of employees stronger.